Reviewing the progress of corrosion fatigue research on marine structures - Yang, Yuefu; Chen, Chaohe; Zhuang, Yifeng; Suo, Zhijia (Frontiers in Materials, 2024)
This paper reviews the state-of-the-art progress of corrosion fatigue research on marine structures in relation to theoretical and experimental studies, including corrosion fatigue life prediction models/methods, load-environment interaction/coupling test methods, accelerated corrosion methods in corrosion fatigue test, fatigue crack measurement and corrosion fatigue life assessment in whole life period. To date, some theoretical models and methods for predicting the corrosion fatigue life of metallic materials or structures have been proposed and applied successively. Meanwhile, the load-environment interaction/coupling test those aim to the metallic material specimens have been maturely developed and widely applied. In the recent years, some newlydeveloping corrosion fatigue theoretical and experimental methods, which based on the data-driven/machine learning and at-sea monitoring have been applied preliminarily. The review on accelerated corrosion methods, fatigue crack measurement methods and corrosion fatigue life assessment for marine structures in whole life period are undertaken by extensively referring related work conducted worldwide. Challenges and recommendations towards further developing and improving corrosion fatigue assessment methods and test techniques are also reported and discussed.